2016
DOI: 10.1111/cdev.12559
|View full text |Cite
|
Sign up to set email alerts
|

Learning in Complex Environments: The Effects of Background Speech on Early Word Learning

Abstract: Although most studies of language learning take place in quiet laboratory settings, everyday language learning occurs under noisy conditions. The current research investigated the effects of background speech on word learning. Both younger (22‐ to 24‐month‐olds; n = 40) and older (28‐ to 30‐month‐olds; n = 40) toddlers successfully learned novel label–object pairings when target speech was 10 dB louder than background speech but not when the signal‐to‐noise ratio (SNR) was 5 dB. Toddlers (28‐ to 30‐month‐olds;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 79 publications
(83 reference statements)
0
26
0
Order By: Relevance
“…Baseline‐adjusting children's accuracy during the critical window would potentially correct for these initial differences. However, in contrast to prior research that has used baseline‐adjusted accuracy (e.g., McMillan & Saffran, ), our baseline differences in accuracy were intentional and therefore much larger. A baseline adjustment of this magnitude would be inappropriate for a bounded measure like accuracy (e.g., for a condition with 30% baseline accuracy, children have the potential to increase their accuracy by 70% during the critical window; for a condition with 50% baseline accuracy, however, children only have the potential to increase their accuracy by 50%).…”
Section: Resultsmentioning
confidence: 70%
“…Baseline‐adjusting children's accuracy during the critical window would potentially correct for these initial differences. However, in contrast to prior research that has used baseline‐adjusted accuracy (e.g., McMillan & Saffran, ), our baseline differences in accuracy were intentional and therefore much larger. A baseline adjustment of this magnitude would be inappropriate for a bounded measure like accuracy (e.g., for a condition with 30% baseline accuracy, children have the potential to increase their accuracy by 70% during the critical window; for a condition with 50% baseline accuracy, however, children only have the potential to increase their accuracy by 50%).…”
Section: Resultsmentioning
confidence: 70%
“…There has been growing interest in understanding the scalability of segmentation tasks to natural learning conditions (e.g. Frank, Tenenbaum, Gibson, & Snyder, 2013; Graf Estes & Lew-Williams, 2015; Lew-Williams & Saffran, 2012; Pelucchi, Hay, & Saffran, 2009), including investigations of how learners process speech with the presence of background noise (Fu & Nogaki, 2005; Mattys, 2004; McMillan & Saffran, 2016). While listeners in quiet conditions can exploit transition statistics and many of the cues listed above, listeners in noisy conditions and listeners with limited access to acoustic hearing are less able to recruit this suite of cues.…”
Section: Discussionmentioning
confidence: 99%
“…Learning costs related to more pleasant background noise have also been shown, as instrumental music can impair learning from television among infants (Barr et al, 2010). Similarly, background speech can disrupt the acquisition of new labels: McMillan and Saffran (2016) found that toddlers struggled to learn new labels unless they were substantially louder than background speech. Although the cause of such difficulties in listening and learning when noise is present is uncertain, early maturation of the auditory system may implicate attentional difficulties (Erickson & Newman, 2017).…”
Section: Implications For Learningmentioning
confidence: 99%